WAYANG PANAKAWAN - Drs. Sunarto, M.Hum (Ars: Jurnal Seni Rupa dan Desain, 2008)
Panakawan is a group character in a wayang ( Javanese traditional puppet show) show. Each panakawan is unique and capable of explaining various roles. The group can be met in various types of wayang in Indonesia. The panakawan special characteristic is that unlike other wayang characters, they have the by design ugly, invalid and unroportional appearances. Since when these characters existed in the Indonesian wayang is unknown. It is necessary to investigate the historical aspect of Panakawan. There are two tracks can be followed in scrutinizing the characters, namely the verbal aspect and the pictorial aspect. In verbal aspect, the data was obtained from notes, writings, literary works, etc in the form of publications or manuscripts. In pictorial aspect, the data is gathered from pictures, things, artifacts, etc.Keywords: panakawan, historical, archelogical